2021
DOI: 10.1111/ijfs.15317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plasma‐activated water and heat moisture treatment on the properties of wheat flour and dough

Abstract: Summary Plasma‐activated water (PAW) production and use is an emerging technology for enhancing product safety, extending shelf‐life and quality retention, and promoting sustainable processing. At present, it has generated considerable attention for applications to starch and flour modification. This work presents an innovative approach to wheat flour (WF) modification using PAW and heat‐moisture treatment (HMT), and compares this approach with distilled water (DW) treatment. As expected, PAW and HMT promoted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Villanueva et al [ 12 ] reported an increase of elastic and viscous moduli when microwave treated rice flour was used in gluten-free bread, explaining that the rearrangements of the amylose and amylopectin chains probably contributed to the dough strengthening. Furthermore, the increase in the visco-elastic moduli could have been promoted by the exposure of hydrophilic groups (–COOH, –NH 2 ) generated by HMT which led to a higher water-binding capacity [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Villanueva et al [ 12 ] reported an increase of elastic and viscous moduli when microwave treated rice flour was used in gluten-free bread, explaining that the rearrangements of the amylose and amylopectin chains probably contributed to the dough strengthening. Furthermore, the increase in the visco-elastic moduli could have been promoted by the exposure of hydrophilic groups (–COOH, –NH 2 ) generated by HMT which led to a higher water-binding capacity [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…The increase of resistant starch in treated wheat pasta compared to untreated pasta is shown in Figure 3 . Protein denaturation occurs when HMT is applied to wheat flour, with the modified molecules being able to adhere on the starch grain aggregates surface to create barriers that slow down the digestive activity of the enzymes [ 13 ]. Furthermore, the formation of amylose-lipid complexes could be another explanation for the RS content increase, since amylose has a helical shape that can encompass fat or other hydrophobic molecules of a small size [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…HMT also promoted a densely packed aggregation structure of starch that prevented digestive enzymes from binding to starch granules. Furthermore, under low-moisture conditions, the proteins were denatured by heat and adhered to the surface of the starch granules, reducing the contact site for digestive enzymes [ 47 ]. The increase in RDS and SDS content was due to the disruption of the ordered structure of the starch molecular chains and the weakening of the interactions between the molecular chains, making the starch granules susceptible to attack by digestive enzymes [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ΔH of PAW-25% sample was the lowest. It may be due to the formation of more heterogeneous crystallites which caused by the acid degradation from plasma activated water ( 16 , 17 ).…”
Section: Resultsmentioning
confidence: 99%